The Measurement of Fast Transient Emissions During Real World Driving - Peckham, Mark; Parnell, Jamie; Hammond, Matthew; Mason, Byron (Frontiers in Mechanical Engineering, 2020)
Some of the most challenging aspects of preparing vehicles to comply with the new RDE (Real Driving Emissions) legislation are the calibration of engines to minimize emissions during numerous short lived transients. Fast response emissions analyzers are necessary to resolve rapid transient emissions and have been deployed simultaneously in the engine-out and tailpipe exhaust gas stream of several vehicles. The methodology presented and capability of the instrumentation enables fine resolution of emissions events leading to the opportunity for fine tuning of controller performance. Data has also been logged from the vehicles' ECUs and combined with accurate GPS data. The results show that certain road lay-outs (e.g., congested junctions and speed bumps) can provoke significant tailpipe NOx emissions; often emitting very high levels near schools where traffic calming measures have been adopted for road safety. The lean excursions and insufficient rich purge during such transients are generally shown to be the cause of such emitting events.